Electrophysiological effects of cimetidine on rabbit myocardium - Zhang Yi; Gang Jing-Min (Acta Pharmacologica Sinica; Vol 13, No 4 (July 1992): Acta Pharmacologica Sinica, 2016)
Effects of cimetidine (Cim) were studied electrophysiologically on fast action potential (AP) in rabbit papillary muscle and slow AP in pacemaker cell of rabbit sinoatrial node (SAN) as well as on atrioventricular (A-V) conduction in anesthetized rabbit. Cim (0.01, 0.1, 1, and 2 mmol.L-1) induced prolongations of AP duration (APD) and effective refractory period (ERP), slowing down of the maximal rate of rise of phase 0 (Vmax) and of the slope of phase 4 depolarization (SP4), and a decrease of AP amplitude (APA) in concentration-dependent manners. Cim (100 mg.kg-1 iv) prolonged the A-V conduction. The results suggest that Cim, like quinidine, shows a membrane stabilizing effect, which may be the electrophysiological basis of the anti-arrhythmic effect of Cim.